Effects of Bi3+ Ion-Doped on the Microstructure and Photoluminescence of La0.97Pr0.03VO4 Phosphor - Chen, Hao-Long; Shih, Hung-Rung; Wu, Sean; Chang, Yee-Shin (Advances in Technology Innovation, 2021)
The objective of this paper is to enhance the emission intensity of La0.97Pr0.03VO4 single-phased white light emitting phosphor. The Bi3+ ion-doped La0.97Pr0.03VO4 single-phased white light emitting phosphors are synthesized using a sol-gel method. The structure and photoluminescence properties of (La0.97-yBiy)Pr0.03VO4 (y = 0-0.05) phosphor are also examined. The XRD results show that the structure of La0.97Pr0.03VO4 phosphors with different concentrations of Bi3+ ion doping keeps the monoclinic structure. The SEM results show that the phosphor particles become smoother when the Bi3+ ion is doped. The excitation band for La0.97Pr0.03VO4 phosphor exhibits a blue shift from 320 nm to 308 nm as the Bi3+ ion contents are increased. The maximum emission intensity is achieved for a Bi3+ ion content of 0.5 mol%, which is about 30% greater than that with no Bi3+ ion doped. The CIE chromaticity coordinates are all located in the near white light region for different Bi3+ ion-doped La0.97Pr0.03VO4 phosphors.